2018
DOI: 10.3201/eid2408.180081
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Expansion of Macrolide-Resistant Sequence Type 3Mycoplasma pneumoniae, South Korea

Abstract: To investigate the genetic background for the emergence of macrolide resistance, we characterized the genetic features of Mycoplasma pneumoniae using multilocus sequence typing. Of the 146 M. pneumoniae strains collected during the 5 consecutive outbreaks of M. pneumoniae pneumonia during 2000–2016 in South Korea, macrolide resistance increased from 0% in the first outbreak to 84.4% in the fifth. Among the 8 sequence types (STs) identified, ST3 (74.7%) was the most prevalent, followed by ST14 (15.1%). Macrolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 33 publications
1
40
2
Order By: Relevance
“…Despite the fact that knowledge about the genotype of a clinically relevant strain has had no consequences for therapy up to now, the relations between resistance and typing markers are of epidemiological interest. Regarding the related species M. pneumoniae, results of different studies indicated a relationship between the occurrence of macrolide resistance as well as the clinical severity of infections with particular sequence or VNTR type strains [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that knowledge about the genotype of a clinically relevant strain has had no consequences for therapy up to now, the relations between resistance and typing markers are of epidemiological interest. Regarding the related species M. pneumoniae, results of different studies indicated a relationship between the occurrence of macrolide resistance as well as the clinical severity of infections with particular sequence or VNTR type strains [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, STs in M. pneumoniae isolates differed by area and year in Japan (1,7,14). Thus, MLST analysis is helpful in understanding worldwide trends among pathogenic M. pneumoniae.…”
Section: Discussionmentioning
confidence: 90%
“…Mycoplasma pneumoniae is a major cause of community-acquired pneumonia, and macrolide-resistant M. pneumoniae is a serious concern in Asia ( 1 – 3 ). Throughout Japan, an outbreak of macrolide-resistant M. pneumoniae infection occurred during 2011–2012 ( 2 ).…”
mentioning
confidence: 99%
“…The comparative whole genome approach was able to define high genetic identity, unique structural diversity, and phylogenetic associations among the 78 M. pneumoniae strains isolated worldwide. pneumoniae pneumonia were defined as previously described (17).…”
Section: Discussionmentioning
confidence: 99%